2023
DOI: 10.1021/acs.jpclett.2c03914
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-Responsive Organic Phosphorescence Materials Based on Small Molecular Host–Guest Doped Systems

Abstract: Small molecular host−guest doped materials exhibit superiority toward highefficiency room-temperature phosphorescence (RTP) materials due to their structural design diversity and ease of preparation. Dynamic RTP materials display excellent characteristics, such as good reversibility, quick response, and tunable luminescence ability, making them applicable to various cutting-edge technologies. Herein, we summarize the advances in host−guest doped dynamic RTP materials that respond to external and internal stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 108 publications
0
24
0
Order By: Relevance
“…In the doped system, although the guest molecules emitted phosphorescence, the host played an indispensable assisting role, and the T 1 state of the host, lying between the S 1 and T 1 states of the guest, acted as a bridge for the exciton transfer of the guests. [32] As shown in Figure 1F, the energy gap between the S 1 and T 1 states of BT was 2.18 eV, and the considerable magnitude of the energy gaps posed a challenge to the process of excitonic ISC. However, the band gaps between the S 1 state of the guest and the T 1 state of the hosts were merely 1.28 and 1.17 eV for BT/PPO and BT/BPO, respectively, which was beneficial for improving the ISC efficiency of excitons.…”
Section: Resultsmentioning
confidence: 99%
“…In the doped system, although the guest molecules emitted phosphorescence, the host played an indispensable assisting role, and the T 1 state of the host, lying between the S 1 and T 1 states of the guest, acted as a bridge for the exciton transfer of the guests. [32] As shown in Figure 1F, the energy gap between the S 1 and T 1 states of BT was 2.18 eV, and the considerable magnitude of the energy gaps posed a challenge to the process of excitonic ISC. However, the band gaps between the S 1 state of the guest and the T 1 state of the hosts were merely 1.28 and 1.17 eV for BT/PPO and BT/BPO, respectively, which was beneficial for improving the ISC efficiency of excitons.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to their advantages such as facile treatment and large‐scale preparation, phosphor‐doped room‐temperature phosphorescence (RTP) polymers have garnered considerable attention, making them a new class of flexible luminescent materials [6–13] . However, recent investigations have revealed that the simultaneous achievement of outstanding afterglow and excellent flexible properties poses a challenge to their applicability [10,14–17] . The triplet excitons from organic phosphors are unstable at room temperature, therefore, a polymer matrix is required to provide a rigid environment.…”
Section: Figurementioning
confidence: 99%
“…Organic light-emitting materials have aroused intense interest in the field of organic optoelectronic devices, 1 chemical sensing, 2 biological imaging, 3 and stimuli response. 4 These materials are used mainly in their solid-state forms, such as crystals, 5 powders, 6 films, 7 and nanoparticles, 8 and with these materials the molecular aggregation effect on the luminescent property cannot be ignored. [9][10][11] However, the complexity of molecular packing structures, such as different packing motifs (e.g., herringbone, long-range π-π stacking) and multiple intermolecular interactions (e.g., π-π, hydrogen bonds, electrostatic interactions, halogen bonds, charge transfer) in aggregates, [12][13][14][15][16] make it difficult to reveal a definite structure-property relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Organic light-emitting materials have aroused intense interest in the field of organic optoelectronic devices, 1 chemical sensing, 2 biological imaging, 3 and stimuli response. 4 These materials are used mainly in their solid-state forms, such as crystals, 5 powders, 6 films, 7 and nanoparticles, 8 and with these materials the molecular aggregation effect on the luminescent property cannot be ignored. 9–11 However, the complexity of molecular packing structures, such as different packing motifs ( e.g.…”
Section: Introductionmentioning
confidence: 99%